The Influence of Work Motivation, Job Insecurity, and Organizational Culture on Turnover Intention at PT Bima Golden Powerindo - Michelle Tayli; Melkyory Andronicus; Bintang Sebastian Limbong; Munawarah Munawarah (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Turnover intention is one of the critical issues in human resource management as it can lead to increased operational costs and decreased organizational productivity. The rising turnover rate at PT Bima Golden Powerindo indicates problems related to work motivation, job insecurity, and organizational culture as perceived by employees. This study aims to analyze the effect of work motivation, job insecurity, and organizational culture on employees’ turnover intention. This study employs a quantitative approach with an explanatory survey design. The sampling technique used is total sampling, with a total of 31 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that partially, work motivation does not have a significant effect on turnover intention (Sig. 0.317 > 0.05). Job insecurity has a positive and significant effect on turnover intention (Sig. 0.023 < 0.05), while organizational culture has a negative and significant effect on turnover intention (Sig. 0.046 < 0.05). Simultaneously, the three variables have a significant effect on turnover intention (Sig. 0.000 < 0.05) with a coefficient of determination (R²) of 0.572. It can be concluded that job insecurity and organizational culture are significant factors influencing turnover intention, while work motivation does not have a significant effect. Therefore, the company is recommended to enhance job security and strengthen organizational culture in order to reduce employees’ turnover intention.